Novel mutations in the exon 5, intron 2 and 3′ UTR regions of IL-12B gene were observed in clinically proven tuberculosis patients of south India - Babu, Pallipamu Prakash; Kumar, Pasupuleti Santhosh; Mohan, Alladi; Kumar, Bhattaram Siddhartha; Sarma, Potukuchi Venkata Gurunadha Krishna (Cytokine (Philadelphia, Pa.), 2017)
•Novel missense mutations observed in the exon 5 of IL-12B gene in NSP-PTB patients.•Frame shift mutations in IL-12B gene causes deletion of functional FN3 domain.•Novel mutations identified in the intron 2 and 3′ UTR region of IL-12B gene.•Decreased expression of IFN-γ and IL-12 levels in NSP-PTB patients compared to HCS. Interleukin-12 (IL-12) is formed by the interaction of IL-12p35 and IL-12p40 expressed independently from IL-12A and IL-12B genes. This interleukin plays prominent role in the T-helper type-1 (Th1) response against intracellular pathogens. Variations in IL-12B gene causes disruption of various activities one of them is suppression of Th1 response and is one of the characteristic features observed in patients with active tuberculosis. Hence, in the present study IL-12B gene status was evaluated in 50 new sputum smear-positive pulmonary tuberculosis patients (NSP-PTB) as identified by Ziehl-Nielsen (ZN) staining and 50 apparently healthy control subjects (HCS) who were sputum smear-negative. The sequence analysis showed novel missense mutations p.Ser205Ile, p.Leu206Glu, p.Pro207Ser, p.Glu209Lys, p.Val210Ser, p.(Ser205_Cys327delinsIleGlu) and p.(Lys217_Leu218delinsIle) were found in exon 5 of the IL-12B gene in nine patients resulting formation of inactive IL-12 and three patients showed novel frame shift mutations p.(Asn222Leufs∗23) in exon 5 of causing the formation of truncated protein. Several mutations were noted in intron 2 of the IL-12B gene in 5 patients and in 13 patients mutations were observed in 3′ UTR region. All together 30/50 patients (60%) showed mutations in IL-12B gene. Decreased levels of interferon-gamma (IFN-γ) and IL-12 as determined by ELISA and flow cytometry were observed in the peripheral blood mononuclear cell culture supernatants in TB patients having mutations compared with control subjects. Further, in silico analysis revealed due to frame shift mutations in exon 5 at Asn222 resulted in deletion of functional fibronectin type-III (FN3) domain which leads to formation of inactive IL-12 in these patients.